Enhancing Regional Integration Through Commercial Ties in the Eastern Neighbourhood of the Eu - Teodor Lucian Moga; Alexandru Cristian Fotea (CES Working Papers, 2012)
Economic unification across Europe has been the main impetus for the European integration process and this rationale stood also behind the European Union (EU) approach towards its neighbourhood. Since the launch of the European Neighbourhood Policy (2004), the economic incentives have been the most effective instruments for generating structural change in the neighbourhood, taking into account the fact that EU membership has not been yet considered. Our research will aim at investigating the potential of the European Union to promote economic cooperation in its Eastern vicinity by seeking to include the Eastern Partnership states into a network that shares the same economic principles and values. Among these values, we argue that deep economic engagement through bilateral and multilateral frameworks of trade relations has played a major in enhancing the economic development of the six-Post Soviet states: Ukraine, Moldova, Belarus, Azerbaijan, Georgia and Armenia.
Keywords: F15; 330; European Neighbourhood Policy; Eastern Partnership; Eastern Europe; trade relations Romania